The development and empirical evaluation of a competency model of trainer-instructor performance : an elaboration on a partial competency model of trainer-instructor performance - Wessels, Annemie (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.